STRATEGI PENDIDIKAN RELIGIUS PADA ANAK PENDERITA AUTISME (STUDI KASUS DI SLB C NEGERI AUTIS KEDUNGKANDANG KOTA MALANG) - Miftah Rizky Eka Putri; Muhammad Hanief; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
Education and science are needed since we young. Without ignoring autistic children, they are same as like us, but they have obstacle to thinking. The existence of autistic children who are still difficult to accept because of their different behavior. Education is important to developing a positive character for autistic children but especially for their religious, one alternative to develop this character can be found at the SLB C Autis Kedungkandang which applied religious education strategies to autistic children. In this study, the researcher used a method with 3 instruments such as interviews, observation and documentation. This study also aims to describe, the learning process, education strategies, and religious education activities in SLB C Autis Malang. The outline results of this study is autistic children will aplly their religious education that they received.. And learning activities are adjusted to the child's ability level.